Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2174/138161207780831301
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein: Interaction with the Vascular Endothelium and Possible Role in Human Atherosclerosis

Abstract: C-reactive protein (CRP) is the first acute phase protein that has been described in the literature. It is phylogenetically ancient and - with serum amyloid P - belongs to proteins named as "pentraxin". After being considered a marker of acute inflammation for several decades and fruitfully used in clinical practice, CRP has been recently considered as a potential contributor to inflammatory diseases including atherosclerosis as well as a marker of cardiovascular risk. With regard to the first topic, inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 170 publications
(273 reference statements)
1
71
0
3
Order By: Relevance
“…CRP has been recently considered as a potential contributor to inflammatory diseases including atherosclerosis as well as a marker of cardiovascular risk (29). More recently, one study showed that low-grade systemic inflammation caused endothelial dysfunction in sHT patients with Hashimoto's thyroiditis (30).…”
Section: Discussionmentioning
confidence: 99%
“…CRP has been recently considered as a potential contributor to inflammatory diseases including atherosclerosis as well as a marker of cardiovascular risk (29). More recently, one study showed that low-grade systemic inflammation caused endothelial dysfunction in sHT patients with Hashimoto's thyroiditis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Initial stages of atherosclerotic vasculopathy are characterized by disruption of the integrity of endothelial monolayer, exposure of the constituents of subendothelial space to the blood flow, recruitment of immune and inflammatory cells into the vascular wall, vascular inflammation and decreased production of vasoprotective agents [4,5]. An interaction of endothelial cells with T-and B-lymphocytes, neutrophils, platelets and numerous immune and inflammatory agents produced by these cells leads toward atherosclerotic plaque formation, its destabilization and rupture [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between circulating levels of CRP and IL-6 and the expression of molecules by endothelial cells has not been adequately investigated so far. Transcription of CRP in the liver is IL-6 dependent (14), and, in turn, the secreted CRP stimulates IL-6 release from the vascular endothelium (46). We hypothesize that this loop occurs in a precise time window and could explain the absence of the IL-6 signal inside endothelial cells in all our IMA specimens.…”
Section: Discussionmentioning
confidence: 82%